Applying Distribution Functions to GWO Algorithm - G. Krishna Mohan, Dr; N. Sai Prasanna, Ms; K. Siva Sai Krishna, Mr; I. Vamsi Krishna, Mr (International Journal of Engineering and Technology, 2018)
GWO is an Optimization algorithm. It depends on the different distribution functions. The features of Optimization algorithm are as follows Convergence, precision, and performance. These Characters will generalize this optimization algorithm. In this paper, we explored GWO algorithm for different distributing functions. There are many distribution functions that are kept practical to the GWO algorithm. We evaluated three different distribution functions which are the Gold Stein function, Beale function and the Booth function. To show the effectiveness of the GWO algorithm we have used the above three distribution functions.Â Â